(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Organ donation means giving your organ - or part of it - to someone who needs it to live. An organ transplant is a surgery to remove an organ from you and place it in someone who needs it. If you are an organ donor, this can happen after you die. But sometimes you can donate your organ while you are alive.